Taxonomy and DNA barcoding of Cyamophila (Hemiptera: Psyllidae) from Japan, with the description of a new species - Inoue, Hiromitsu (Zootaxa, 2025)
The jumping plant-lice of the genus Cyamophila from Japan are reviewed. Three species are recognized. The new species, Cyamophila burckhardti sp. nov. is described. One new synonym is proposed: Cyamophila hexastigma (Horváth) = Cyamophila floribundae Cho & Burckhardt syn. nov. Cyamophila hexastigma and C. willieti (Wu) are redescribed, and the latter is newly recorded from Japan. Keys to species for adults and immatures, diagnoses, biological information, and DNA barcoding results are provided.